The digital gender divide. A focus on inclusion through mobile phone use in India - Tusińska, Magdalena (Wydawnictwo Uniwersytetu Rzeszowskiego, 2021)
Due to the growing use of ICTs in all areas of life, the means to access these technologies and skills to operate them are regarded as important prerequisites for social inclusion or, more specifically, e-inclusion. In developing states, mobile connectivity has become an important way for people to access the internet since smartphones are more affordable than computers and break down such access barriers as costs of infrastructure, equipment and required skills. The aim of the article is to present the benefits and limitations of digital inclusion through mobile access from a gender perspective and to investigate the barriers to this process. The research is undertaken from an Indian perspective. The theses verified are: 1) mobile access can represent a pragmatic solution to the digital divide, including the digital gender divide, even if mobile-only internet use does not necessarily lead to complete e-inclusion, 2) due to the nature of barriers to access, the digital gender divide remains a persistent problem in India. The research methods used were literature review, analysis of statistical data, online sources and elements of a case study. Access to mobile devices and the internet are not gender-neutral in India. There are a number of root causes of the digital gender divide, including financial constraints, technological illiteracy, as well as socio-cultural norms. Therefore, government and business activities should focus on these areas.

Ze względu na rosnące wykorzystanie ICTs we wszystkich dziedzinach życia, posiadanie urządzeń umożliwiających dostęp do tych technologii i umiejętności ich obsługi są uważane za warunki wstępne włączenia społecznego, a dokładniej e-inkluzji. W krajach rozwijających się ważnym sposobem uzyskiwania dostępu do Internetu stała się telefonia komórkowa, ponieważ smartfony są tańsze niż komputery i wydają się znosić bariery dostępu, takie jak koszty infrastruktury, sprzętu i wymaganych umiejętności. W tym kontekście celem artykułu jest przedstawienie korzyści i ograniczeń integracji cyfrowej poprzez dostęp mobilny z perspektywy płci oraz zbadanie barier tego procesu z perspektywy Indii. Podjęto się weryfikacji dwóch hipotez: 1) dostęp mobilny może stanowić pragmatyczne rozwiązanie problemu luki cyfrowej (w tym ze względu na płeć), nawet jeśli korzystanie wyłącznie z urządzeń mobilnych niekoniecznie prowadzi do pełnej e-integracji, 2) ze względu na specyfikę barier w dostępie, cyfrowa luka między płciami pozostaje aktualnym problemem w Indiach. Zastosowane metody badawcze to krytyka literatury, analiza danych statystycznych, analiza źródeł internetowych oraz elementy studium przypadku. Stwierdzono, że w Indiach dostęp zarówno do urządzeń mobilnych, jak i do Internetu, nie jest neutralny pod względem płci. Wśród ważnych przyczyn tej sytuacji można wskazać ograniczenia finansowe, brak umiejętności, a także normy społeczno-kulturowe. Działania rządu i biznesu powinny zatem koncentrować się na tych obszarach.
Keywords: digital gender divide; e-inclusion; gender equality; mobile phones; internet; luka cyfrowa; e-inkluzja; równość płci; telefony komórkowe; Internet